Affibody Molecules Intended for Receptor-Mediated Transcytosis via the Transferrin Receptor - Linnea Charlotta Hjelm; Hanna Lindberg; Stefan Ståhl; John Löfblom (Pharmaceuticals, 2023)
The development of biologics for diseases affecting the central nervous system has been less successful compared to other disease areas, in part due to the challenge of delivering drugs to the brain. The most well-investigated and successful strategy for increasing brain uptake of biological drugs is using receptor-mediated transcytosis over the blood–brain barrier and, in particular, targeting the transferrin receptor-1 (TfR). Here, affibody molecules are selected for TfR using phage display technology. The two most interesting candidates demonstrated binding to human TfR, cross-reactivity to the murine orthologue, non-competitive binding with human transferrin, and binding to TfR-expressing brain endothelial cell lines. Single amino acid mutagenesis of the affibody molecules revealed the binding contribution of individual residues and was used to develop second-generation variants with improved properties. The second-generation variants were further analyzed and showed an ability for transcytosis in an in vitro transwell assay. The new TfR-specific affibody molecules have the potential for the development of small brain shuttles for increasing the uptake of various compounds to the central nervous system and thus warrant further investigations.